2017
DOI: 10.1080/2162402x.2017.1321186
|View full text |Cite
|
Sign up to set email alerts
|

Immune classifications with cytotoxic CD8+ and Th17 infiltrates are predictors of clinical prognosis in glioblastoma

Abstract: Our study shows that glioblastoma bearing patients can be classified on the immune infiltrate aspects. Beyond this prognostic role of immune biomarkers, subsequent classifications could definitely help clinicians to handle targeted therapy administration and immunotherapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
(36 reference statements)
4
23
0
Order By: Relevance
“…The gene signatures proposed by Becht et al have been carefully selected to be specific for the described immune cell populations and validated in several thousand tumors including a small dataset of medulloblastoma. 26 A study of CD8 and Th17 infiltrates in GBM 30 showed comparable associations with prognosis of immunohistological data and data based on gene expression signatures in a similar approach to those proposed by Becht et al Further, intratumoral heterogeneity of gene expression in medulloblastoma is very low, 31 which also supports our assumption that transcriptome based analysis is suitable for a global description of the tumor microenvironment. However, it cannot be excluded that tumor cells contribute to the expression score, which might significantly confound the analysis.…”
Section: Discussionsupporting
confidence: 84%
“…The gene signatures proposed by Becht et al have been carefully selected to be specific for the described immune cell populations and validated in several thousand tumors including a small dataset of medulloblastoma. 26 A study of CD8 and Th17 infiltrates in GBM 30 showed comparable associations with prognosis of immunohistological data and data based on gene expression signatures in a similar approach to those proposed by Becht et al Further, intratumoral heterogeneity of gene expression in medulloblastoma is very low, 31 which also supports our assumption that transcriptome based analysis is suitable for a global description of the tumor microenvironment. However, it cannot be excluded that tumor cells contribute to the expression score, which might significantly confound the analysis.…”
Section: Discussionsupporting
confidence: 84%
“…PD‐L1 expression in combination with CD8 + T infiltration could be a better predictor of OS. It has also been shown that cytotoxic CD8 + lymphocytes cells infiltrations were associated with a good prognosis in GBM 41 . In this study, immunohistochemical results indicated that both PD‐L1 expression and CD8 + T lymphocytes in GBM were closely related to the prognosis of patients.…”
Section: Discussionsupporting
confidence: 51%
“…It has also been shown that cytotoxic CD8 + lymphocytes cells infiltrations were associated with a good prognosis in GBM. 41 In this study, immunohistochemical results in- 22 In this study, high expressions of EGFR, CSN6, and PD-L1…”
Section: Discussionmentioning
confidence: 67%
“…Although there are several studies carried out to investigate the potential role of IL‐17A in the progression of malignant GBMs, the mechanism of IL‐17A could influence glioma progression remains unclear. In GBM patients, high IL‐17A infiltration is associated with poorer prognosis, suggesting it as a potential prognosis factor . Previously, it has been reported by other group that IL‐17A protein expression is increased in traumatic brain injury group compared with the sham‐operated group in a rat model .…”
Section: Discussionmentioning
confidence: 90%
“…It improves the transition from chronic pancreatitis to pancreatic cancer through the novel REG3β‐JAK2‐STAT3 inflammatory pathway . IL‐17A is frequently observed in many cancers such as ovarian cancer, gastric cancer, and hepatocellular carcinoma, and being reported to associate with a poor clinical outcome in patients with GBM . Higher level of IL‐17A is found in glioma tissues as compared with trauma tissues, however, the role of IL‐17A in migration and invasion of GBM cells is not fully illuminated and the mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%